Portela Cafés: your home since 1977 - Crespo de Carvalho, J. (Economia Global e Gestão, 2012)
The Portela Cafés case study is centred in the development of a chain of stores with origins in Portugal and a core business focused on coffee (production to distribution) and service but also offering complementary products such as chocolates, pastry, meals, teas and others. Specifically, the general idea of the business venture is to develop a chain of coffee retail stores and complementary products where one quickly becomes aware that despite the wide and varied range of products, service is what is at the heart of the company and coffee is somehow its soul. Currently with seven stores, Portela Cafés is facing a huge dilemma in strategic terms: growing seems to be the future in part because Portela Cafés has an excess of installed capacity in terms of coffee roasting, filling and packaging and also in the capsule filling format (coffee and tea) of distribution; on the other hand, the central question seems to be ?is there enough market to sustain a growing chain that aims to be differentiated and practicing some market skimming??